1999
DOI: 10.1074/jbc.274.38.26850
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of an E1A-sensitive Coactivator for Long-range Transactivation by the β-Globin Locus Control Region

Abstract: Four erythroid-specific DNase I-hypersensitive sites at the 5-end of the ␤-globin locus confer high-level transcription to the ␤-globin genes. To identify coactivators that mediate long-range transactivation by this locus control region (LCR), we assessed the influence of E1A, an inhibitor of the CBP/p300 histone acetylase, on LCR function. E1A strongly inhibited transactivation of A␥-and ␤-globin promoters by the HS2, HS2-HS3, and HS1-HS4 subregions of the LCR in human K562 and mouse erythroleukemia cells. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 54 publications
2
47
0
Order By: Relevance
“…Because the purification was conducted under high stringency conditions, it is not surprising that only the high affinity leucine zipper-mediated p45/NF-E2-p18 interaction was preserved. Even though CBP/ p300 interacts with p45/NF-E2 with moderate affinity and high specificity in vitro, and the CBP/p300 inhibitor E1A abrogates NF-E2-mediated transactivation (50), endogenous p45/NF-E2 has not been co-purified with endogenous CBP/p300. A simple explanation for these results is that the high salt used to extract NF-E2 from nuclei dissociates NF-E2-co-regulator interactions.…”
Section: Despite the Impaired Chromatin Modification And Pol II Recrumentioning
confidence: 99%
See 2 more Smart Citations
“…Because the purification was conducted under high stringency conditions, it is not surprising that only the high affinity leucine zipper-mediated p45/NF-E2-p18 interaction was preserved. Even though CBP/ p300 interacts with p45/NF-E2 with moderate affinity and high specificity in vitro, and the CBP/p300 inhibitor E1A abrogates NF-E2-mediated transactivation (50), endogenous p45/NF-E2 has not been co-purified with endogenous CBP/p300. A simple explanation for these results is that the high salt used to extract NF-E2 from nuclei dissociates NF-E2-co-regulator interactions.…”
Section: Despite the Impaired Chromatin Modification And Pol II Recrumentioning
confidence: 99%
“…An obvious step in transactivation in which the PXY-1 mutant might be compromised is CBP/p300 recruitment, because CBP/ p300 mediates NF-E2-dependent transactivation in transient transfection assays (49,50). CBP/p300 is also a mediator of GATA-1-dependent transactivation (60).…”
Section: Despite the Impaired Chromatin Modification And Pol II Recrumentioning
confidence: 99%
See 1 more Smart Citation
“…CBP acetylates GATA-1 (Hung et al, 1999) and increases NF-E2 DNA binding activity (Hung et al, 2001). Studies with E1A also indicated that CBP/p300 is crucial for LCRmediated transactivation (Forsberg et al, 1999a). CBP/ p300 acetylates EKLF, which enhances EKLF binding to the SWI/SNF complex (Zhang et al, 2001;Letting et al, 2003;Im et al, 2005;Kim et al, 2007).…”
Section: Fog-1mentioning
confidence: 99%
“…Furthermore, CBP and p300 have distinct functions in T-cell lymphopoiesis (Kasper et al, 2006). CBP/p300 physically and functionally interact with many transcription factors, including GATA-1, p45/NF-E2 and EKLF (Blobel et al, 1998;Zhang and Bieker, 1998;Forsberg et al, 1999a). Studies with the CBP/p300 inhibitor adenoviral E1A provided evidence that CBP/ p300 facilitates GATA-1-mediated transcriptional activity and promotes erythroid differentiation (Blobel et al, 1998).…”
Section: Fog-1mentioning
confidence: 99%